1999
DOI: 10.1063/1.124799
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting phosphorescence in Ce3+-doped Ca2Al2SiO7 and CaYAl3O7 crystals

Abstract: Long-lasting phosphorescence is observed in Ce3+-doped Ca2Al2SiO7 (CASM) and CaYAl3O7 (CYAM) crystals at room temperature. UV irradiation at 365 nm produces broadband emissions with peaks at 417 nm for CASM and 425 nm for CYAM, which persist for not less than 1 h after the removal of the irradiating light. Based on the time dependence of the intensity of the phosphorescence, the long-lasting phosphorescence in these crystals is considered to be due to the electron–hole recombination at shallow traps, which occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
59
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(65 citation statements)
references
References 9 publications
2
59
1
Order By: Relevance
“…Malinowski et al [15] have studied the spectroscopy properties of Dy 3+ -doped SrLaGa 3 O 7 crystals. Long-lasting phosphorescences have also been reported recently in CaYAl 3 O 7 :Ce 3+ (CYAM) [16,17], CaYAl 3 O 7 :Eu 2+ , Dy 3+ [18] and CaGdAl 3 O 7 :Eu 2+ , Dy 3+ [18] melilite crystals. Flahaut and co-workers [19] have shown that the thiogallates MLaGa 3 S 7 (M = Ca, Sr) and La 5/3 Ga 3 S 7 have the structure of melilite.…”
Section: Introductionmentioning
confidence: 89%
“…Malinowski et al [15] have studied the spectroscopy properties of Dy 3+ -doped SrLaGa 3 O 7 crystals. Long-lasting phosphorescences have also been reported recently in CaYAl 3 O 7 :Ce 3+ (CYAM) [16,17], CaYAl 3 O 7 :Eu 2+ , Dy 3+ [18] and CaGdAl 3 O 7 :Eu 2+ , Dy 3+ [18] melilite crystals. Flahaut and co-workers [19] have shown that the thiogallates MLaGa 3 S 7 (M = Ca, Sr) and La 5/3 Ga 3 S 7 have the structure of melilite.…”
Section: Introductionmentioning
confidence: 89%
“…Long-persistence phosphorescence in Ce 3+ doped Ca 2 Al 2 SiO 7 with a melilite structure has been reported recently by Kodama et al [2,3]. Ce 3+ functions as a high-efficiency emission center because 4f-5d transitions * Corresponding author.…”
Section: Introductionmentioning
confidence: 94%
“…The slurry method is the most common method, in which phosphor powder is mixed with photosensitive chemicals and is patterned using photolithography techniques. For operating voltages greater than 2 kV, the screen is back coated with a thin layer of aluminium which acts as an optical reflector as well as a charge dissipater [20][21][22]. At operating voltage below 2 kV, the electron penetration depth is so small that the screens are left un-coated [23][24][25].…”
Section: Introductionmentioning
confidence: 99%